Revision of the Triassic European turtles Proterochersis and Murrhardtia (Reptilia, Testudinata, Proterochersidae), with the description of new taxa from Poland and Germany. (20th May 2016) - Szczygielski, Tomasz; Sulej, Tomasz
Abstract : A recently discovered Norian outcrop in Poręba, Poland, has yielded numerous well‐preserved turtle remains. These, together with historical materials from Germany, enabled the identification of two new proterochersid taxa: Proterochersis porebensis sp. nov. from Poland and Keuperotesta limendorsa gen. et sp. nov. from Germany. Moreover, two problematic taxa, Proterochersis intermedia Fraas, 1913; and Murrhardtia staeschei Karl & Tichy, 2000; are shown to be conspecific with Proterochersis robusta Fraas, 1913. New diagnoses for the family Proterochersidae Nopcsa, 1923 and all included taxa are provided. Proterochersids are of great importance to turtle phylogeny because of their age (they comprise the oldest fully shelled turtle species known to date) and their still‐debated phylogenetic position (classically they are considered the basalmost Pleurodira, but in some analyses they are placed on the stem of Testudinata). Newly discovered plesiomorphic aspects of the anatomy of these three species included in the phylogenetic analysis demonstrate that they are not only the oldest, but are also the most basal fully shelled turtles. The unique features of their shell (e.g. the first thoracic rib unreduced and costal‐bearing, and the osseous contact between the carapace and sacral vertebra) are of special significance for future research of the earliest stages of turtle shell evolution. This is the first contribution focused solely on the new, phylogenetically informative, and important characters of this group since the initial description of P. robusta more than 100 years ago.